(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The paper aims to assess how public support for innovation activities influences the economic performance of Czech companies. In the framework of the research, attention was paid to more than 600 Czech companies that received support to start their innovation activities. The analysis was performed on the case of the Innovation Program, which was co-financed by the European Regional Development Fund. The Innovation Program is the largest Czech program for innovation support and mainly supports the launching of technological innovations in practice. The detailed analysis included 214 defined enterprises, for which all necessary information was available. The research analyzed the turnover of companies before obtaining support and after the implementation of the project. The research results show how the grant affects different size categories of enterprises and how the effect of the aid varies across sectors of the national economy.